The Effect of Optimum Injector Position on the Humidification Process of Steadily Flowing Air Stream in a Cross Varying Duct (Journal of University of Babylon for Engineering Sciences, 2018)
Experimental and numerical investigations are carried out on the use of water injection in a humidification process of air traveling steadily through the divergent part of a wind tunnel. This work aims to study the optimum positioning of the water injector fixed at a divergent portion and to evaluate its impact on the liquid-gas mixing in an air humidification process. Experiments are conducted in a 50 cm square wind tunnel includes a gradually enlarged portion to 63 cm square having an air stream flowing at mean velocity of 5 m/s agrees with Reynolds number of 1.5X105 .This study adopts a mass flow ratio in a range of 300 to 600, and ambient temperatures between 30oC and 45oC. Experimental results showed that at any location within the divergent portion, the optimum position is realized when directing the spray towards the core of the flow which achieves the best humidification and cooling of the air. The optimum position for the single injection point is at the center of the duct with the axial direction of flow, i.e. at a yawing angle of 0o. As the injector moves close to the wall, the cooling getting poorer. At the ambient temperature of 45oC and flow ratio of 300, the maximum increase in relative humidity was 43.8%, corresponding to maximum cooling extent of 15.2% when the injector was fixed at 50 cm prior to the divergent portion. The study also implies a numerical analysis using ANSYS FLUENT 17.0 commercial CFD package, used to validate the conformity between experimental and numerical results obtained at the same operational conditions.